Anticipating the outcomes: how young adults with developmental disabilities and co-occurring mental health conditions make decisions about disclosure of their mental health conditions at work. Issue 4 (13th February 2023) - Schwartz, Ariel E.; Corey, Jesse; Duff, Jenna; Herer, Alix; Rogers, E. Sally
Abstract: Purpose: Little is known about how young adults (YA) with developmental disabilities (DD) and co-occurring mental health conditions navigate workplace disclosure of their mental health condition(s). We sought to understand the guidance professionals provide regarding disclosure and the decisions YA makes about disclosure of mental health conditions. Methods: We conducted focus groups with professionals who support YA with DD to attain and maintain employment ( n  = 17) and individual interviews with YA with DD and co-occurring mental health conditions ( n  = 12; DD diagnoses: autism, n  = 9, other DD, n  = 3). We conducted content analysis to identify why, when, what, and to whom YA disclose their mental health condition and guidance provided regarding disclosure. Results: YA and professionals described disclosure decisions as largely influenced by perceived needs (i.e., need for accommodations) and anticipated positive (e.g., support) and negative (e.g., stigma, not being hired) outcomes. They largely constrained disclosure to work-relevant content. Many YA disclosed to coworkers with whom they were comfortable, though both YA and professionals agreed that initial disclosure should be limited to supervisors and/or human resources. Conclusions: Workplaces may support disclosure—a necessity for the provision of accommodations—by cultivating an inclusive environment and openly demonstrating familiarity and comfort with employees with disabilities. IMPLICATIONS FOR REHABILITATION: Professionals who support young adults with developmental disabilities and co-occurring mental health conditions should be well-versed in current laws and regulations on disclosure and reasonable workplace accommodations. Workplace culture is one major factor impacting how disclosure is handled, including whether the disclosure is required at all. Individuals with disabilities and professionals should recognize that timing, content, and decisions to disclose may vary by individuals' needs and workplace supports, and that change may occur over time.